QUALITY OF WORK LIFE OF FEMALE NURSES - Jain, Sumita; Kapur, Dr. Surbhi (The journal of contemporary issues in business and government, 2022)
At the conclusion of each day, working women in government and private hospitals have the issue of balancing their professional responsibilities with their obligations to their families. The majority of women work full-time, and 53 percent of them are having trouble striking a healthy balance between their professional and personal lives. As a result of having to juggle many duties at work and at home, many women have complained that their lives have grown increasingly complicated. They can foster an environment of support to assist these women in striking a healthy balance between their professional and personal lives. The authors of this study investigate the quality of work-life balance of female nurses.